KONFLIK AMERIKA SERIKAT DAN IRAN PASCA-TERBUNUHNYA KEPALA KORPS QUDS GARDA REVOLUSI IRAN MAYOR JENDERAL QASEM SOLEIMANI PADA 2020 - Devih Desdian Dwihendra; Tom Finaldin (Global Mind, 2020)
AbstractDevih Desdian Dwi Hendra, C1A170167, Conflict of the United States and Iran       Post-Killing of the Head of the Quds. Corps of the Iranian Revolutionary Guard Major General Qasem Soleimani In 2020, Faculty of Social and Political Sciences International Relations Studies Program Al-Ghifari University, 2020, Advisor Tom Finaldin, A.Md., SIP, M.Sc..The purpose of this study is to examine the extent to which the attacks carried out by the United States againts Iran on the orders of President Donald Trump, which killed the head of the Iranian Revolutionary Guard Quds Corps Major General Qasem Soleimani were actually motivated by US interests alone. Even if the reason given is to stop the war and not to start a war and save from a major attack on the citizens of the United States in the Middle East, the US therefore prevents it by attacking first. The results of this study indicate that in this conflict case, the United States has violated international law. There are two things that are volated by the United States. Firts, it violates international law, commits assassinations of other countries in a state of non-war and secondly, violates agreements between Iraq and America itself, which include no violation of sovereignty. Despite the loss of an influential military leader, the death of Mayor General Qasem Soleimani could benefit Iran in the short term. Iran has the opportunity to show its ability to unite in times of crisis, unite the political elite that has been divided. Thus the realization of national interests for the future in the aspirations of its people as a sovereign nation. Keywords : Conflict, United States, Iran